MORPHOLOGICAL FEATURES OF THE PLACENTA AND VAGINAL MICROBIOCENOSIS IN WOMEN WITH PREMATURE BIRTH - Татьяна Юрьевна Марочко; Максим Владимирович Додонов; Людмила Александровна Леванова; Владимир Анатольевич Артымук (The Publishing House Medicine and Enlightenment, 2019)
Objective - to assess the morphological features of the structure of the placenta and the state of the microflora of the vagina and placenta in women with preterm birth. Materials and methods. Study design: retrospective, case-control. The study included 150 women. Group I consisted of 50 women with premature vaginal birth; Group II consisted of 100 women with term vaginal birth. Results. The results of the study showed that in patients with preterm birth (PB), an ascending infection of the placenta is realized with a predominance of choriodeciduitis (40 %) and intervillusitis (32 %), as well as a higher rate of placental insufficiency (54 %). In these women in the early stages of pregnancy, a higher incidence of vaginal biocenosis was recorded. The relationship between the vaginal biocenosis in early pregnancy, the frequency of infection of the surface of the placenta and the realization of infection of the placenta has not been established. In patients with PB in the early stages of pregnancy, statistically significantly more often microorganisms were isolated from the vagina such as Staphylococcus haemolyticus - 30.6 %, Staphylococcus epidermidis - 30.6 %, Corynbacterium spp. - 19.4 %, Enterococcus faecalis, E. coli. No statistically significant differences were found between the frequency of excretion of various microorganisms from the surface of the placenta in women with preterm and term births. Conclusion. Patients with PB were characterized by a higher incidence of ascending infection of the placenta and disorders of vaginal biocenosis.